Local dose-dense chemotherapy for triple-negative breast cancer via minimally invasive implantation of 3D printed devices - Noehyun Myung; Hyun-Wook Kang (Elsevier, 2024)
Dose-dense chemotherapy is the preferred first-line therapy for triple-negative breast cancer (TNBC), a highly aggressive disease with a poor prognosis. This treatment uses the same drug doses as conventional chemotherapy but with shorter dosing intervals, allowing for promising clinical outcomes with intensive treatment. However, the frequent systemic administration used for this treatment results in systemic toxicity and low patient compliance, limiting therapeutic efficacy and clinical benefit. Here, we report local dose-dense chemotherapy to treat TNBC by implanting 3D printed devices with time-programmed pulsatile release profiles. The implantable device can control the time between drug releases based on its internal microstructure design, which can be used to control dose density. The device is made of biodegradable materials for clinical convenience and designed for minimally invasive implantation via a trocar. Dose density variation of local chemotherapy using programmable release enhances anti-cancer effects in vitro and in vivo. Under the same dose density conditions, device-based chemotherapy shows a higher anti-cancer effect and less toxic response than intratumoral injection. We demonstrate local chemotherapy utilizing the implantable device that simulates the drug dose, number of releases, and treatment duration of the dose-dense AC (doxorubicin and cyclophosphamide) regimen preferred for TNBC treatment. Dose density modulation inhibits tumor growth, metastasis, and the expression of drug resistance-related proteins, including p-glycoprotein and breast cancer resistance protein. To the best of our knowledge, local dose-dense chemotherapy has not been reported, and our strategy can be expected to be utilized as a novel alternative to conventional therapies and improve anti-cancer efficiency.